Atmospheric nitrogen deposition in Yangtze River Delta: insights gained from the nitrogen content and isotopic composition of the moss Haplocladium microphyllum. Issue 3 (3rd May 2020) - CHEN, Zhili; HUANG, Tao; FAN, Rong; YANG, Hao; YANG, Yanju; HUANG, Changchun
ABSTRACT: Simple and inexpensive estimation of the rates and sources of atmospheric nitrogen (N) deposition is critical for its effective mitigation in a region with different land-use types. In this study, the N content and N isotopic composition (δ 15 N) of moss ( Haplocladium microphyllum ) tissues and precipitation at six sites with three land-use types (urban, suburban, and rural) were measured in the Yangtze River Delta. A significant linear relationship between moss N content and wet N deposition, and a consistent decrease trend for moss N content and wet N deposition from urban to suburban to rural areas were observed. More negative δ 15 N of suburban and rural mosses indicated N mainly released from agriculture and effluent, while the less negative δ 15 N of urban mosses were mainly influenced by fossil fuel combustion and traffic emissions. Although the negative moss δ 15 N indicates that reduced N dominates wet N deposition, there was no significant correlation between moss δ 15 N and the ratio of ammonium to nitrate (NH4 + /NO3 − ). These results reveal that the moss N content and δ 15 N can be used as a complementary tool for estimating the rates and sources of wet N deposition in a region with different land-use types. Graphical abstract: